Expanding the clinical spectrum of the 'HDAC8‐phenotype' – implications for molecular diagnostics, counseling and risk prediction. Issue 5 (25th January 2016) - Parenti, I.; Gervasini, C.; Pozojevic, J.; Wendt, K.S.; Watrin, E.; Azzollini, J.; Braunholz, D.; Buiting, K.; Cereda, A.; Engels, H.; Garavelli, L.; Glazar, R.; et al.
Abstract : Cornelia de Lange syndrome (CdLS) is a clinically heterogeneous disorder characterized by typical facial dysmorphism, cognitive impairment and multiple congenital anomalies. Approximately 75% of patients carry a variant in one of the five cohesin‐related genes NIPBL, SMC1A, SMC3, RAD21 and HDAC8 . Herein we report on the clinical and molecular characterization of 11 patients carrying 10 distinct variants in HDAC8 . Given the high number of variants identified so far, we advise sequencing of HDAC8 as an indispensable part of the routine molecular diagnostic for patients with CdLS or CdLS‐overlapping features. The phenotype of our patients is very broad, whereas males tend to be more severely affected than females, who instead often present with less canonical CdLS features. The extensive clinical variability observed in the heterozygous females might be at least partially associated with a completely skewed X‐inactivation, observed in seven out of eight female patients. Our cohort also includes two affected siblings whose unaffected mother was found to be mosaic for the causative mutation inherited to both affected children. This further supports the urgent need for an integration of highly sensitive sequencing technology to allow an appropriate molecular diagnostic, genetic counseling and risk prediction. Abstract :